Margaret Pelli: A Geriatric Standardized Patient Case - Matthew Gentile; Kevin Overbeck; Pamela Basehore; Anita Chopra; Kathy Alburger (Association of American Medical Colleges, 2013)
Abstract Introduction The Margeret Pelli standardized patient (SP) case was developed at the University of Medicine and Dentistry of New Jersey's School of Osteopathic Medicine (UMDNJ-SOM) to be one of three possible SP cases used in the medical student's year two geriatrics course. Experts in the field of geriatrics and standardized patient case development played a major role from initial planning to completion of the project. Methods All related case materials were designed by the team assembled to create this case. The case was developed to provide students an opportunity and scenario in which they can demonstrate competence with the Mini Mental Status Exam (MMSE) and the Clock Drawing Test. After the exam room encounter, students are given a SOAP note form to fill out in a different room. The case is scored by a second standardized patient who views the encounter. Results The case has been utilized in both the 2011 and 2012 medical students' year two geriatrics courses at UMDNJ-SOM. Faculty members who make up our undergraduate education team have assessed this case both during creation, and on a yearly review basis. Comments and scoring about this encounter are consistently positive, with the majority of students applauding the detailed experience. Discussion Successful execution of the SP role requires the SP to study and commit to memory the details of the patient's life and illness complaint. SPs are required to attend training sessions on a regular basis to ensure validity and reliability in case performance. The Margaret Pelli case has been subjected to quality assurance checks to assess accuracy and fidelity in SP performance. The director of the lab, along with lab staff, review the case to compare the performance of the SP to the patient script which they are directed to follow.